Mobile Applications, An Emerging Powerful Tool for Dyslexia Screening and Intervention: A Systematic Literature Review - Politi-Georgousi, Stratigoula; Drigas, Athanasios (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Nowadays, mobile applications seem to play a vital role in both dyslexia screening and intervention, accumulating numerous assets and comforts in according to dyslexics’ needs and learning pace. Initial detection of students’ disabilities, followed by a corresponding intervention program were the best combination of actions in an attempt to any problem be confronted effectively. In our today’s society, mobile apps have been considered as an alternative approach for the success of these well-known key steps, as well. The aim of this literature review is to propose a great number of screening and treatment mobile applications for dyslexia. During the last decades these have been developed or have been implemented, focused on different aspects of dyslexia symptoms (reading, writing, mathematical difficulties, memory etc.) The studies are categorized into two sections, based on the purpose for which mobile applications are used at a time. The first part reflects a mobile app as a detection tool, while the second part presents it as intervention tool.